Genomic characterisation of emerging Enterococcus faecium vanA types from 2013 to 2020 in an Australian public hospital - Ronan F. O'Toole; Vitalie Covalciuc; Ana Cooke; Gaetan Thilliez; Emma K. Finlay; Kelvin W.C. Leong; Vanessa Farthing; Sebastiaan J. van Hal (Journal of Global Antimicrobial Resistance)
Objective: High rates of resistance to vancomycin are now being reported among invasive isolates of Enterococcus faecium, a major cause of healthcare-associated infections globally. The objective of this study was to generate a better understanding of emerging vanA sequence types (ST) of the pathogen. Methods: A temporal analysis of isolates collected from 2013 to 2020 at the Royal Prince Alfred Hospital, a large Australian hospital, was performed using genome sequencing. Relative frequencies of multi-locus ST, antibiotic resistance markers, and virulence genes were determined. Results: ST1421 was the dominant vanA ST from 2014 to 2018. ST1424, which was not evident in the 2013 and 2014 isolates, emerged in 2016 and became the dominant vanA type in 2020 (65% of isolates). vanA ST80 was less common among the Royal Prince Alfred Hospital vanA isolates. Direct comparison of 120 genomes of each ST revealed significantly higher encoded resistance to aminocyclitols (e.g. spectinomycin) and folate-pathway antagonists (e.g. trimethoprim) in ST1421 and ST1424 compared to ST80. Furthermore, significantly higher carriage of enterococcal virulence genes ecbA (E. faecium collagen binding protein A) and hylEfm (glycosyl hydrolase) was found in ST1421 and ST1424 than in ST80. Conclusions: Newer vanA ST ST1421 and ST1424 harboured several antibiotic resistance loci and virulence genes at significantly higher levels than those observed in ST80. Ongoing genomic surveillance is warranted for the detection of new variants of E. faecium and characterisation of their encoded resistance and virulence.